PERKEMBANGAN POPULASI JALAK PUTIH (Sturnus melanopterus Daudin 1800) DI TAMAN NASIONAL BALI BARAT - Dwitantian Hawa Brillianti (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Black-winged starling (Sturnus melanopterus Daudin 1800) has spread across West Bali National Park (WBNP). There are three subspecies of black-winged starling; Sturnus melanopterus tertius is distributed in the area of Bali, Sturnus melanopterus tricolor is distributed in East Java, and Sturnus melanopterus melanopterus is distributed  in East Java and Madura. Status of black-winged starling was Critically Endangered in 2010. Therefore, this study aimed to (1) analyze the populations (numbers, sex ratio, and age structure) and analyze habitats of black-winged starling in West Bali National Park. Bird population was estimated by transect and concentration count method and black-winged starling habitat condition was identified using vegetation analysis. The result showed that the estimation of black-winged starling population were 35 individuals, sex ratio was 1:1, and all individuals were adults. The habitat which often used by black-winged starling was savanna as feeding area, drinking area, shelter area, and cover area.Keywords: black-winged starling, Bali barat, habitat, population